Sport as a Tool for Education: Developing Skills for Life - Abdukodir, Ismatov (Journal of Innovation in Education and Social Research, 2025)
Sports play a crucial role in education, extending beyond physical fitness to develop essential life skills such as teamwork, leadership, discipline, and resilience. Integrating sports into the educational system fosters cognitive and social development, enhancing students' academic performance, emotional intelligence, and career readiness. This article explores how sports contribute to holistic education, emphasizing their impact on personal growth, social integration, and lifelong learning. By examining global practices and successful models, the paper highlights the importance of structured sports programs in shaping well-rounded individuals prepared for future challenges.